(untitled) (Eurasian Scientific Herald, 2022)
The language plays a very important role in our life. Out presidents have been paying much attention to learn languages, especially, English since the independence. So nearly all people know the language. They help us express our emotions. They help us explain what we want and to communicate and hence are the prime tools to express who we are. Thus the knowledge of a language and its proper utilization is very important as it defines us. If languages were not there to help us communicate there would be no difference in our communications and the way the animals communicate.